On transformations involving generalized basic hypergeometric function of two variables - R. Yadav; S. Purohit; V. Vyas (Revista Técnica de la Facultad de Ingeniería, 2012)
In the present paper, transformations for basic analogue of the Fox”™s H-function of one and two variables have been derived by the application of the q-Leibniz rule for the product of two basic functions. Some special cases involving a basic analogue of Meijer”™s G-function are also derived.